Unloved bull markets : getting rich the easy way by riding bull markets - Callahan, Craig (John Wiley & Sons, Inc., 2022)
"From the low on March 9, 2009, to the bull market peak February 19, 2020, the S&P 1500 Index gained 530.1%, meaning $1.00 invested at the bottom would have grown into $6.30. This truly qualifies as a great bull market, yet many investors didn't participate and even sold and avoided the equities. To show that the 2009 multi-year bull market was unloved, the authors will examine mutual fund flows, investor sentiment, public pension funds, Barron's confidence index, and stock-bond yields There is an old saying, "make hay while the sun shines." The counterpart for investing would be "make money in bull markets," but investors failed to do so during the last two bull markets. For a variety of reasons, many pension plans, money managers, financial advisors and investors held cash, didn't realize bull markets were under way, and squandered billions of dollars. Why? For thirty-six years, working as discretionary portfolio managers, the authors have been telling financial advisors and investors "rallies and bull markets don't issue invitations" and "rallies and bull markets don't look like rallies and bull markets" . . . until they are over. As bull markets climb a wall of worry, this book will help financial advisors and investors focus on the profitable climb instead of the worries."--